Revamping Technopreneurship Education in Public Higher University - Haryanti, Nor; Nor, Md; Maziah, Siti; Rahman, Abdul; Hayati, Yusrina; Muhammad Naziman, Nik; Norbaya, Siti; Rashid, Mohd; Farleena, Nadia; Aznan, Mohd (International Journal of Engineering and Technology, 2018)
Envisioning new innovation strategy, it is wisely to fostering the technopreneurship area of education in public higher education. To be an entrpreneurial universities, it initiate to have a focus on undergraduate student starting from enrollment to graduation, which offered constant encouragement, training and support for their efforts to conceive and start up business enterprises with prototype they conceive. In this regards, this paper examines a factors required by the universities in bolstering the better prelude efforts towards the students in technopreneurship by indicating the competition, technology transfer and university policy.Â Sample of study was taken from undergraduate students at public university involving 146 students which already been taught the technopreneurship course at university. The descriptive statistics, multiple regression analysis and t-test were used to investigate the effect factors.Â In line with previous studies, the results reveal that competition, technology transfer and university policy statically significant in influencing the technopreneurship education at university. Surprisingly, the study shows that competition plays a crucial part in enhancing a better lookout in this innovation. The exposure from competition will drive them to be a creative person in nature and laterally develop an entrepreneurship skill in future. The result is useful for policy makers as well as university in considering the effect of these 3 factors in the eyes of undergraduates.Â Exploratory in nature, globalization and surge demand on technopreneurship thus evolve the trend in vibrant economic growth, industrialize and development context. Â Â Â Â